2012
DOI: 10.1007/s00540-012-1493-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate attenuates tourniquet pain in healthy volunteers

Abstract: Magnesium sulfate, 4 g, significantly attenuated tourniquet pain in healthy awake volunteers, suggesting that NMDA receptor activation is involved in tourniquet pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…8 The use of an N-methyl-d-aspartate receptor antagonist, magnesium sulphate, given intravenously has also been shown to reduce tourniquet pain. 9 In addition, it reduced the degree of blood pressure rise seen in patients undergoing procedures under tourniquet.…”
Section: Oxygen Reduces Tourniquet-associated Pain: a Double-blind Rmentioning
confidence: 99%
“…Some studies indicated that the NMDA receptor activation produced increases in mean arterial pressure while the NMDA receptor antagonism blocked the cardiovascular response in animals [20]. Some NMDA receptor antagonists could attenuate tourniquet-induced pain and hypertension under general anesthesia as reported in previous studies [5,8,9,21] as the NMDA receptor antagonists could prevent central sensitization that occurs due to peripheral nociceptive stimulation [19]. Tourniquet pain may occur during spinal or epidural anesthesia despite adequate sensory block, and its occurrence is more frequently observed during epidural anesthesia than spinal anesthesia [4].…”
Section: Discussionmentioning
confidence: 71%
“…Various NMDA receptor antagonists were used to manage tourniquet pain and TIH [5,[7][8][9]. Other drugs and methods were used to reduce tourniquet effects such as the use of regional anesthesia, intravenous (IV) opioids, paracetamol, gabapentin, non-steroidal anti-inflammatory drugs (NSAIDs), melatonin and clonidine which has been reported to depress nerve action potentials in c-fibers [10].…”
Section: Introductionmentioning
confidence: 99%